Does Hand-Dominance Matter in Non-Standard Visuomotor Transformations?. Issue 5 (3rd September 2021) - Jones, Briasha D.; Van Gemmert, Arend W. A.; Dalecki, Marc
Abstract: Previous nonstandard visuomotor transformation studies using variations of eye-hand coupling and decoupling tasks focused on dominant hand use. The present study expanded this work by including the non-dominant hand. Twenty-four right-hand dominant adults (M = 21 yrs.; 12 females) slid their index finger along a vertical or horizontal touchscreen to move a cursor that was always displayed in the vertical plane. In four different action-perception conditions, the finger and cursor moved either in the same plane and direction or in the other plane and/or opposite direction. Performance differed between the hands only for movement trajectory related variables but not for endpoint related measures. Across conditions the initial direction error was larger when performing with the non-dominant hand (p < 0.001). A significant hand × cursor direction × cursor plane interaction for path length (p < 0.05) revealed longer movement trajectories for the non-dominant hand compared to the dominant hand in conditions with none or one level of eye-hand decoupling, and similar hand performance when movements were made in the horizontal plane with reversed cursor direction, i.e., two eye-hand decoupling levels. Our findings suggest a non-dominant hand overall eye-hand coordination deficit for spatial planning and an inversely related deficit to the eye-hand decoupling level for trajectory execution.